\documentclass[12pt]{article} \usepackage{ntnu} \usepackage{ntnu-math} \author{Øystein Tveit} \title{MA0301 Exercise 4} \usepackage{amsthm} \begin{document} \ntnuTitle{} \break{} \begin{excs} \exc{} \begin{subexcs} \subexc{} \begin{gather*} \overline{xy} + \overline{x}\ \overline{y} \\ \overline{1 \cdot 0} + (\overline{1}\cdot \overline{0}) \\ \overline{0} + (0 \cdot 1) \\ 1 + 0 \\ 1 \end{gather*} \subexc{} \begin{gather*} w + \overline{x}y \\ 1 + (\overline{1} \cdot 0) \\ 1 + 0 \\ 1 \end{gather*} \subexc{} \begin{gather*} wx + \overline{y} + yz \\ (1 \cdot 1) + \overline{0} + (0 \cdot 0) \\ 1 + 1 + 0 \\ 1 \end{gather*} \subexc{} \begin{gather*} (wx + y\overline{z}) + w\overline{y} + \overline{(w + y)(\overline{x} + y)} \\ ((1 \cdot 1) + (0 \cdot \overline{0})) + (1 \cdot \overline{0}) + \overline{(1 + 0)(\overline{1} + 0)} \\ (1 + 0) + (1 \cdot 1) + \overline{(1)(0 + 0)} \\ 1 + 1 + \overline{(1)(0)} \\ 1 + 1 + \overline{0} \\ 1 + 1 + 1 \\ 1 \end{gather*} \end{subexcs} \exc{} \begin{subexcs} \subexc{} \begin{gather*} xy + (x + y)\overline{z} + y \\ (xy + y) + \overline{z}x + \overline{z}y \\ y + \overline{z}x + \overline{z}y \\ \overline{z}x + (y + \overline{z}y) \\ \overline{z}x + y \end{gather*} \subexc{} \begin{gather*} x + y + \overline{(\overline{x} + y + z)} \\ x + y + \overline{\overline{x}}\ \overline{y}\ \overline{z} \\ x + y + x\overline{y}\ \overline{z} \\ (x + x\overline{y}\ \overline{z}) + y \\ x + y \end{gather*} \subexc{} \begin{gather*} yz + wx + z +[wz(xy + wz)] \\ (yz + z) + wx + (xywz + wz) \\ (z + xywz + wz) + wx \\ z + wx \end{gather*} \end{subexcs} \exc{}{} Base case \begin{align*} \sum^{1}_{i=0}i^2 &= \frac{1 \cdot (1 + 1)(2 \cdot 1 + 1)}{6} \\[2ex] 1^2 &=\frac{2 \cdot 3}{6} \\[2ex] 1 &=\frac{6}{6} \\[2ex] 1 &= 1 \end{align*} Assume: \[ \sum^{k}_{i=0}i^2 = \frac{k (k + 1)(2k + 1)}{6} \] \begin{align*} \sum^{k+1}_{i=0}i^2 &= 0^2 + 1^2 + 2^2 + \ldots + k^2 + (k + 1)^2 \\[2ex] &= \frac{k (k + 1)(2k + 1)}{6} + (k + 1)^2 \\[2ex] &= \frac{k (k + 1)(2k + 1) + 6(k + 1)^2}{6} \\[2ex] &= \frac{ (k + 1)(k (2k + 1) + 6(k + 1))}{6} \\[2ex] &= \frac{ (k + 1)(2k^2 + k + 6k + 6)}{6} \\[2ex] &= \frac{ (k + 1)(2k^2 + 7k + 6)}{6} \\[2ex] &= \frac{ (k + 1)(k + 2)(2k + 3)}{6} \\[2ex] &= \frac{(k + 1) ((k + 1) + 1)(2(k + 1) + 1)}{6} \end{align*} \qed \exc{} \begin{subexcs} \subexc{} \begin{align*} S(0) &= 2^{-0} = 1 \\ S(1) &= 2^{-0} + 2^{-1} = 1.5 \\ S(2) &= 2^{-0} + 2^{-1} + 2^{-2} = 1.75 \\ S(3) &= 2^{-0} + 2^{-1} + 2^{-2} + 2^{-3} = 1.875 \end{align*} \subexc{} Based on the results from a, I conjecture that \[ S(n) = 2 - 2^{-n} \] \subexc{} Base case \begin{align*} \sum^{0}_{i=0}2^{-i} &= 2-2^{-0} \\ 2^{-0} &= 2-1 \\ 1 &= 1 \end{align*} Assume: \[ \sum^{n}_{i=0}2^{-i} = 2-2^{-n} \] \begin{align*} \sum^{n+1}_{i=0}2^{-i} &= 2^{-0} + 2^{-1} + 2^{-2} + \ldots + 2^{-n} + 2^{-(n+1)} \\ &= 2-2^{-n} + 2^{-(n+1)} \\ &= 2-2^{-n} + 2^{-n-1} \\ &= 2-2^{-n} + 2^{-n}2^{-1} \\ &= 2-2^{-n}(1-2^{-1}) \\ &= 2-2^{-n}(\frac{2}{2}-\frac{1}{2}) \\ &= 2-2^{-n}(\frac{1}{2}) \\ &= 2-2^{-n}(2^{-1}) \\ &= 2-2^{-n-1} \\ &= 2-2^{-(n+1)} \end{align*} \qed \subexc{} \begin{align*} S(n) &> \epsilon \\ 2-2^{-n} &> \epsilon \\ 2^{-n} &> \epsilon - 2 \\ -n &> \log_2(\epsilon - 2) \\ n &< -\log_2(\epsilon - 2) \\ \end{align*} Assuming $S(n)$ never can reach n, for $S(n)$ to be within $\epsilon$ of $2$, n has to be less than $-\log_2(\epsilon - 2)$ \end{subexcs} \exc{} Base case \begin{align*} \sum^{1}_{i=1}2^{i-1} \cdot i &= 2^n \cdot (n-1) + 1 \\ 2^{1-1} \cdot 1 &= 2^1 \cdot (1-1) + 1 \\ 2^0 \cdot 1 &= 2 \cdot 0 + 1 \\ 1 \cdot 1 &= 1 \\ 1 &= 1 \end{align*} Assume: \[ \sum^{n}_{i=1}2^{i-1} \cdot i = 2^n \cdot (n-1) + 1 \] \begin{align*} \sum^{n+1}_{i=1}2^{i-1} \cdot i &= (2^{1-1} \cdot 1) + (2^{2-1} \cdot 2) + \ldots + (2^{n-1} \cdot n) + (2^{(n+1)-1} \cdot (n+1)) \\ &= 2^n \cdot (n-1) + 1 + (2^{(n+1)-1} \cdot (n+1)) \\ &= 2^n \cdot (n-1) + 1 + 2^{n} \cdot (n+1) \\ &= (2^n \cdot n - 2^n) + 1 + (2^{n} \cdot n + 2^{n}) \\ &= 2^n \cdot n - 2^n + 1 + 2^{n} \cdot n + 2^{n} \\ &= 2(2^n \cdot n) - 2^n + 2^{n}+ 1 \\ &= (4^n \cdot n) + 1 \\ &= (2^{n+1} \cdot ((n+1)-1)) + 1 \end{align*} \qed \end{excs} \end{document}